The SOA/VOC/NOx system: an explicit model of secondary organic aerosol formation - S. Madronich; J. Lee-Taylor; B. Aumont; M. Camredon (Atmospheric Chemistry and Physics, 2007)
Our current understanding of secondary organic aerosol (SOA) formation is limited by our knowledge of gaseous secondary organics involved in gas/particle partitioning. The objective of this study is to explore (i) the potential for products of multiple oxidation steps contributing to SOA, and (ii) the evolution of the SOA/VOC/NOx system. We developed an explicit model based on the coupling of detailed gas-phase oxidation schemes with a thermodynamic condensation module. Such a model allows prediction of SOA mass and speciation on the basis of first principles. The SOA/VOC/NOx system is studied for the oxidation of 1-octene under atmospherically relevant concentrations. In this study, gaseous oxidation of octene is simulated to lead to SOA formation. Contributors to SOA formation are shown to be formed via multiple oxidation steps of the parent hydrocarbon. The behaviour of the SOA/VOC/NOx system simulated using the explicit model agrees with general tendencies observed during laboratory chamber experiments. This explicit modelling of SOA formation appears as a useful exploratory tool to (i) support interpretations of SOA formation observed in laboratory chamber experiments, (ii) give some insights on SOA formation under atmospherically relevant conditions and (iii) investigate implications for the regional/global lifetimes of the SOA.